A Comparative Analysis of Health-Related Quality of Life 1 Year Following Myomectomy or Uterine Artery Embolization: Findings from the COMPARE-UF Registry - Anchan, Raymond M; Wojdyla, Daniel; Bortoletto, Pietro; Terry, Kathryn; Disler, Emily; Milne, Ankrish; Gargiulo, Antonio; Petrozza, John; Brook, Olga; Srouji, Serene; Morton, Cynthia C; Greenberg, James; et al. (Journal of women's health (Larchmont, N.Y. 2002), 2023)
To compare 12-month post-treatment health-related quality of life (HR-QoL) and symptom severity (SS) changes among patients with symptomatic uterine fibroids (SUF) not seeking fertility and undergo a hysterectomy, abdominal myomectomy (AM), or uterine artery embolization (UAE). The Comparing Options for Management: Patient-Centered Results for Uterine Fibroids (COMPARE-UF) Registry is a multi-institutional prospective observational cohort study of patients treated for SUF. A subset of 1465 women 31-45 years of age, who underwent either hysterectomy ( = 741), AM ( = 446), or UAE ( = 155) were included in this analysis. Demographics, fibroid history, and symptoms were obtained by baseline questionnaires and at 1 year post-treatment. Results were stratified by all treatments and propensity score weighting to adjust for differences in baseline characteristics. Women undergoing UAE reported the lowest baseline HR-QoL and highest SS scores (mean = 40.6 [standard deviation (SD) = 23.8]; 62.3 [SD = 24.2]) followed by hysterectomy (44.3 [24.3]; 59.8 [SD = 24.1]). At 12 months, women who underwent a hysterectomy experienced the largest change in both HR-QoL (48.7 [26.2]) and SS (51.9 [25.6]) followed by other uterine-sparing treatments. Propensity score weighting revealed all treatments produced substantial improvement, with hysterectomy patients reporting the highest HR-QoL score (92.0 [17.8]) compared with myomectomy (86.7 [17.2]) and UAE (82.6 [21.5]) ( < 0.0001). Similarly, hysterectomy patients reported the lowest SS scores (8.2 [15.1]) compared with myomectomy (16.5 [15.1]) and UAE (19.6 [17.5]) ( < 0.0001). All procedures showed improvement in HR-QoL and reduction in SS score at 12 months, hysterectomy showing maximum improvement. Of importance, at 12 months, patients who underwent either a myomectomy or UAE reported comparable symptom relief and HR-QoL. Clinicaltrials.Gov Identifier: NCT02260752.